Directed differentiation of bovine trophoblast stem cells: A useful in vitro model for placenta development - Abdallah W. Abdelhady; Sarayut Winuthayanon; M. Sofia Ortega; Andrew M. Kelleher; Thomas E. Spencer (Proceedings of the National Academy of Sciences, 2026)
Cattle have a synepitheliochorial type of placenta characterized by placental cotyledons and maternal endometrial caruncles forming placentomes that are essential for fetal development to term. As the elongated conceptus begins implantation, binucleated trophoblast giant cells (TGC) begin to appear in the chorion. The TGC are hypothesized to arise from progenitor UNC through endoreplication and express unique placenta-specific genes, including placental lactogen (CSH2), pregnancy-associated glycoproteins (PAGs), and prolactin like proteins (PRPs). Despite their essential role in placental cotyledon development and placental function, the cellular and molecular mechanisms regulating trophoblast differentiation in the bovine placenta remain undefined. Here, a differentiation protocol was developed that enabled bovine trophoblast stem cells (TSCs) to generate TGC. The morphologically distinct TGCs were binucleated with a cytoplasm containing abundant secretory granules. Expression of TGC marker genes (CSH2, PAGs, PRPs) was increased in differentiated TSCs. Single-cell transcriptome analysis revealed distinct developmental programs underlying TGC lineage specification. To interrogate regulatory mechanisms governing TGC differentiation, bovine TSCs were engineered to enable inducible GCM1 (glial cells missing 1) expression. Induction of GCM1 during TSC differentiation increased TGC number and TGC-specific gene expression. This robust and tractable in vitro TSC differentiation system is useful to explore trophoblast differentiation and provide fundamental insights into the cellular and molecular mechanisms regulating placenta development in cattle.